EXPERIMENTS ON INTERACTIVE METHODS AND DIGITIZATION OF LESSONS IN HEIS - Najmiddinov Faxriddin Obidovich (Galaxy International Interdisciplinary Research Journal, 2024)
In this article, the characteristics of the educational process in higher educational institutions, as well as the importance of universities in society and economy are changing rapidly. All over the world, universities are competing with each other to attract students, teachers and financial resources. In such a competition, higher education institutions that keep up with the times and use new digital opportunities are gaining an advantage over others.